Group VI metal complexes of tris(diphenylphosphinomethyl)phenylborate: modulation of ligand donation via coordination of M(CO)3 units at the borate phenyl substituent. Issue 8 (21st January 2015) - Fischer, Paul J.; Weberg, Alexander B.; Bohrmann, Trent D.; Xu, Hanyue; Young, Victor G.
Abstract : Modulation of tris(diphenylphosphinomethyl)phenylborate donation to κ 3 -phosphine-bound fragments is inductively achieved by the coordination of 12-electron M(CO)3 fragments at the borate phenyl substituent. Abstract : A series of d 6 metal complexes of tris(diphenylphosphinomethyl)phenylborate ([PhB(CH2 PPh2 )3 ] −, PhBP3 ), including [Et4 N][M(CO)3 (PhBP3 )] (M = Cr, Mo, W), inaugural group VI metal tris(phosphino)borate complexes, and zwitterionic Mn(CO)3 (PhBP3 ) have been synthesized and fully characterized. An analysis of IR ν (CO) data for [Et4 N][M(CO)3 (PhBP3 )] indicates that PhBP3 is significantly less strongly donating than Tp towards zerovalent M(CO)3 fragments; PhBP3 does not function as a strongly donating scorpionate in this system as its does towards cationic metal fragments suggesting that PhBP3 may not function as an effective surrogate of hydrotris(1-pyrazolyl)borate towards zerovalent metals. While the metal centers of [Et4 N][M(CO)3 (PhBP3 )] are very likely still more electron-rich than those of M(CO)3 (triphos), the anions of [Et4 N][M(CO)3 (PhBP3 )] do not provide robust oxidative addition products analogous to those of M(CO)3 (triphos). A new bi-functional role for PhBP3 was investigated via the synthesis of seven structurally characterized bimetallics in which zerovalent M(CO)3 and monovalent [Mn(CO)3 ] + fragments bind the three phosphine atoms and the borate phenyl substituent. IR ν (CO) data support modest attenuation of PhBP3 donor ability at phosphorus upon η 6 -phenyl substituent binding, representing a new inductive strategy for tuning tris(phosphino)phenylborate donation at the κ 3 -phosphine-bound metal fragment.